Reconstruction for diverse fronto-orbital defects with computer-assisted designed and computer-assisted manufactured PEEK implants in one-stage operation: Case reports. Issue 40 (8th October 2021) - Yang, Min; Wu, Zhangyi; Yu, Hai; Cheng, Jun
Abstract: Rational: Reconstruction of complex craniofacial defects in fronto-orbital region has been reported to be extremely few. In this study, we report 2 cases with fronto-orbital defects of different etiologies in one-stage surgical reconstruction with polyetheretherketone (PEEK) prosthesis using computer-assisted design and computer-assisted manufactured (CAD–CAM) techniques. Patient concerns: One patient was a 49-year-old man, who admitted with a depressed and comminuted fracture in the left fronto-orbital region as a result of a motor vehicle collision. The other patient was a 45-year-old woman who was hospitalized with an unexpected diagnosis of a fronto-orbital bone tumor during a head CT examination in a minor traumatic brain injury. None of them had a significant past medical history. Diagnoses: The first patient's head computed tomography (CT) showed multiple depressed comminuted fractures in the right fronto-orbital region with localized frontal lobe contusion, and the diagnosis was clear when combined with the mechanism of traumatic head injuries. The second patient's head CT and magnetic resonance image suggested a right lateral orbital neoplastic lesion that distorted peripheral bone, the postoperative pathological examination demonstrated an osteoma with fibromatous hyperplasia, and thus the women's diagnosis was confirmed. Interventions: A three-dimensional image of both patients' skull bone were collected from a high-resolution CT. A virtual surgical planning for lesion excision and defect remodeling based on CAD–CAM techniques was undertaken, and than the reconstruction surgery was performed in a single procedure using PEEK prosthesis. Antibacterial treatment was prescribed routinely. Outcomes: Postoperatively, both patients achieved excellent aesthetic restoration as well as functional recovery of the orbital cavity without neurological or infectious complications during an average 22 months follow-up. Lessons: The CAD–CAM PEEK implants could be a preferred option for reconstruction of patients with various complex fronto-orbital defects.